METHODS FOR ENHANCING SAFETY AND RELIABILITY IN HYDRAULIC STRUCTURES - Khalimov Ibrokhimjon (Modern American Journals, 2025)
This article presents a comprehensive review and critical analysis of advanced methods for enhancing the safety and reliability of hydraulic structures, such as dams, canals, weirs, and flood control systems. Drawing upon the latest international research, practical case studies, and regulatory frameworks, the article explores the full spectrum of contemporary risk management approaches—from structural and non-structural measures, digital monitoring, and predictive modeling to asset management, institutional frameworks, and emergency preparedness. Special attention is given to the integration of probabilistic and scenario-based design, real-time instrumentation, digital twins, and artificial intelligence for structural health monitoring. Lessons learned from notable failures and best practices in both developed and developing countries are synthesized, including insights from Uzbekistan’s water infrastructure modernization. The article concludes with actionable recommendations for engineers, policymakers, and operators, emphasizing the need for adaptive, multi-layered, and holistic strategies to ensure the long-term safety and resilience of hydraulic structures in the face of aging assets, climate variability, and evolving societal demands.
Keywords: Hydraulic structures; safety; reliability; risk assessment; structural health monitoring; digital technologies; asset management; emergency planning; Uzbekistan; sustainability.